2015
DOI: 10.5539/ass.v11n25p111
|View full text |Cite
|
Sign up to set email alerts
|

Individual, Organizational and Environmental Factors Affecting Work-Life Balance

Abstract: Work-life balance is very important among employee and employers in organizations. Imbalance in work-life will create a lot problem in terms of life satisfaction and workplace satisfaction. This paper is to discuss a study regarding the influence of emotional, spiritual intelligence, organizational support job engagement and technology advancement on employees work-life balance. The findings showed that emotional intelligence, job engagement and organizational support were found positively and significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…Work overload is the perception of having too much to do [104,105] and can impact negatively on productivity [106], reduce organizational commitment, and increase absenteeism due to illness [107]. Various studies [106,[108][109][110][111][112][113][114][115][116] have associated work overload with high levels of work-family conflict [117]. People who are often working from home change their working hours and experience an increased likelihood of interruptions and distractions because of the presence of their family, especially during the COVID-19 pandemic [118].…”
Section: Teleworking Overload Effects On Work-family Conflict and Burnoutmentioning
confidence: 99%
“…Work overload is the perception of having too much to do [104,105] and can impact negatively on productivity [106], reduce organizational commitment, and increase absenteeism due to illness [107]. Various studies [106,[108][109][110][111][112][113][114][115][116] have associated work overload with high levels of work-family conflict [117]. People who are often working from home change their working hours and experience an increased likelihood of interruptions and distractions because of the presence of their family, especially during the COVID-19 pandemic [118].…”
Section: Teleworking Overload Effects On Work-family Conflict and Burnoutmentioning
confidence: 99%
“…This study reinforces the results of previous studies, which found out that emotional intelligence had a significant positive effect on the work-life balance of the employees. This is also reinforced by [37], who stated that emotional intelligence is very important to get the work-life balance of employees. By having emotional intelligence, then someone has the intelligence to understand the emotions of others.…”
Section: The Effect Of Emotional Intelligence On Work-life Balancementioning
confidence: 92%
“…Considering the "human characteristics" in risk assessment all the three dimensions of matching job to the person should be considered, which are the job, individual factors and the organization (Andrew & Sofian, 2012;Kumarasamy et al, 2015;Martin & Schinke, 1998).…”
Section: A Holistic Approach -Taking Into Account Human Characteristicsmentioning
confidence: 99%